Soil Bacterial Community in the Multiple Cropping System Increased Grain Yield Within 40 Cultivation Years - Chen, Tao; Hu, Ruiwen; Zheng, Zhongyi; Yang, Jiayi; Fan, Huan; Deng, Xiaoqiang; Yao, Wang; Wang, Qiming; Peng, Shuguang; Li, Juan (Frontiers in Plant Science, 2021)
The shortage of land resources restricts the sustainable development of agricultural production. Multiple cropping has been widely used in southern China, but whether the continuous planting will cause a decline of soil quality and crop yield is unclear. To test whether multiple cropping could increase grain yield, we investigated the farmlands with different cultivation years (10-20 years, 20-40 years, and > 40 years). Results showed that tobacco-rice multiple cropping rotation significantly increased soil pH, nitrogen nutrient content and grain yield, and increased the richness of bacterial community. The farmland with 20~40 years of cultivation has the highest soil organic carbon (SOC), ammonium nitrogen and grain yield, but there is no significant difference in the diversity and structure of bacterial community in farmland with different cultivation years. The molecular ecological network indicated that the stability of bacterial community decreased across with the cultivation years, which may result in a decline of farmland yields in multiple cropping system > 40 years. The Acidobacteria members as the keystone taxa (Zi ≥2.5 or Pi ≥0.62) appeared in the tobacco-rice multiple cropping rotation farmland, and the highest abundance of Acidobacteria was found in the farmland with the highest SOC and ammonium nitrogen content, suggesting Acidobacteria Gp4, GP7, GP12 and GP17 are important taxa involved in the soil carbon and nitrogen cycle. Therefore, in this study, the multiple cropping system for 20 years will not reduce the crop production potential, but it cannot last for more than 40 years. This study provides insights for ensuring soil quality and enhancing sustainable agricultural production capacity.